Calsyntenins Function as Synaptogenic Adhesion Molecules in Concert with Neurexins - Um, Ji Won (2014)
Multiple synaptic adhesion molecules govern synapse formation. Here, we propose calsyntenin-3/alcadein-β as a synapse organizer that specifically induces presynaptic differentiation in heterologous synapse-formation assays. Calsyntenin-3 (CST-3) was highly expressed during various postnatal periods of mouse brain development. The simultaneous knockdown of all three CSTs, but not CST-3 alone, decreased inhibitory, but not excitatory, synapse densities in cultured hippocampal neurons. Moreover, the knockdown of CSTs specifically reduced inhibitory synaptic transmission in vitro and in vivo. Remarkably, the loss of CSTs induced a concomitant decrease in neuron soma size in a non-cell-autonomous manner. Furthermore, α-neurexins (α-Nrxs) were affinity-purified as components of a CST-3 complex involved in CST-3-mediated presynaptic differentiation. However, CST-3 did not directly bind to Nrxs. Viewed together, these data suggest that the three CSTs redundantly regulate inhibitory synapse formation, inhibitory synapse function, and neuron development in concert with Nrxs.